Service Delivery of Health Information Management Professionals in Tertiary Hospitals, Bayelsa State, Nigeria (Lead City International Journal of Library, Information & Communication Sciences, 2025)
Service delivery is the primary focus of every organisation, and as such Health information management professionals are obliged to this decisive role through constant interaction with patients. This role can only be acted upon expeditiously if practitioners are service delivery conscious and recognizing patients as kings. In a situation where this is not adhered to, there is every propensity that health information management professionals will face service delivery protest. The objective of this study is to evaluate the level of service delivery (SD) of health information professionals in tertiary hospitals in Bayelsa state. Descriptive study design was adopted; population consists of 78 health information management professionals and two focus group of patients in tertiary hospitals in Bayelsa state who served as the sample size. Total enumeration sampling technique was adopted as the sampling size was small for the study. Data collected was analysed using descriptive and inferential statistics. Service delivery is measured on four constructs of Intangibility, Ideology, Limits and Variability based on theory of Human service delivery. The study revealed that the service delivery of health information management professionals in tertiary hospitals in Bayelsa state is very low with an aggregate mean of 0.72. The study therefore recommends that organisational heads of tertiary hospitals should train and retrain health information management professionals that promote service delivery ideology.